2021
DOI: 10.1007/s00520-021-06147-3
|View full text |Cite
|
Sign up to set email alerts
|

A new proactive virtual resource center navigation model identifies patient risk factors to reduce barriers to cancer care during the COVID-19 pandemic

Abstract: Purpose The COVID-19 pandemic has exacerbated cancer treatment disparities, including accessibility to resources. We describe the process and outcomes of a new proactive, virtual nurse-led, resource center navigation model enhanced by using volunteer patient navigators. Using known patient risk factors, this model provides interventions to reduce barriers to care, with an emphasis on non-English-speaking populations. Methods Patients were included if they (1) were in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
2
13
0
4
Order By: Relevance
“…An important study limitation is that we did not explore the patient perspective—healthcare providers and healthcare users have different views on how and why they use a given service, and both are important to inform program planning and referral practices. However, our results were consistent with the patient perspective reported by previous studies, which reduces the chance of having missed vital insights [ 30 , 31 ]. Future research should investigate whether the identified factors are generalizable to other navigation settings and jurisdictions (particularly elsewhere in Canada) with varying navigator roles and responsibilities [ 33 ], the prevalence of these factors among a general cancer population and whether a quantitative association can be observed between these factors and use of CPN services (among NS patients and elsewhere).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…An important study limitation is that we did not explore the patient perspective—healthcare providers and healthcare users have different views on how and why they use a given service, and both are important to inform program planning and referral practices. However, our results were consistent with the patient perspective reported by previous studies, which reduces the chance of having missed vital insights [ 30 , 31 ]. Future research should investigate whether the identified factors are generalizable to other navigation settings and jurisdictions (particularly elsewhere in Canada) with varying navigator roles and responsibilities [ 33 ], the prevalence of these factors among a general cancer population and whether a quantitative association can be observed between these factors and use of CPN services (among NS patients and elsewhere).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the existing evidence on patient navigation programs [3] and the goals of the original patient navigation program, established in 1990 in Harlem, NY [32]. Overall, there is strong evidence from our study, prior studies [3,14,30,31] and the historical circumstances of the first patient navigation program [32] that patients' sociodemographic and psychological factors influence their need for navigation, and thus should act as triggers for program referral. Further, CPN training should continue to emphasize training for the psychosocial, practical and emotional support roles that address the needs associated with these factors.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations